Writing and understanding poetry for teachers and students : a heart's craft - Keyworth, Suzanne, 1948-; Robison, Cassandra (Rowman and Littlefield, 2015)
This book can be used by instructors as the structure for their literature/poetry classes, it can be studied and enjoyed by lovers of poetry to increase their knowledge of the fundamentals, or it can be used in an English, reading, or creative writing classroom. Throughout the book powerful poems serve as models of how poems create meaning and what devices they use in the craft. Each chapter is designed to strategically move from model to guided practice.